Redefining Masculinity in Africa: The Case of Boys and Men with Disabilities in Zimbabwe - Maruzani, Bhasera; Maruzani, Nyevero (International Journal of Humanity and Social Sciences, 2025)
Purpose: The transition from boyhood to manhood in Africa is influenced by the complex interplay of gender, culture, and disability. Boys with disabilities often encounter social exclusion, which hinders their ability to align with traditional masculine ideals associated with strength and self-reliance. This marginalisation diminishes their educational, economic, and social prospects, trapping them in cycles of poverty and dependence. This study investigated the lived experiences of boys and men with disabilities in Africa, underscoring the necessity for inclusive policies that challenge entrenched stereotypes of masculinity. Methodology: Utilising qualitative research methods such as interviews and focus group discussions, the study captured diverse perspectives. The social model of disability guided the study. This model highlights how societal barriers contribute to disabling experiences. Findings indicated that cultural expectations linking masculinity to physical strength further alienated boys with disabilities. However, there is potential for redefining masculinity to encompass emotional resilience and vulnerability, paving the way for greater inclusivity. Unique Contribution to Theory, Policy and Practice: Recommendations included enhancing teacher training programs and launching community outreach initiatives to combat negative stereotypes. Additionally, policies should focus on improving educational and vocational opportunities for boys and men with disabilities, facilitating their full participation in society. There is need to acknowledge the unique experiences of boys and men with disabilities in fostering gender equality and sustainable development in Africa. By promoting inclusive approaches that challenge traditional gender norms, society can create an environment where all individuals can thrive equally.